A SIMULATE PLANT GROWTH RESPONSE TO BIOCHAR ON UPLAND RICE-COWPEA INTERCROP IN A FERRIC LUVISOLS SOIL IN GHANA (Proceedings of the International Conference on Agriculture, 2022)
A field experiment was conducted on a ferric luvisols in the Guinea Savannah zone, to compare the growth and yield of rice-cowpea intercrop in which three different biochar sources (groundnut shells, poultry manure, and corn cobs) was enhanced with inorganic fertilizer to boost their cowpea N and P content and were integrated into the soil at a rate of 5 t ha-1 with a depth of 20 cm. It was carried out in 2018-2019 cropping season. A randomized complete block with 4 replications was used. The Agricultural Production Systems Simulator (APSIM) was tested against this dataset. The effect of biochar treatments greatly increases growth of rice. The model performed better in simulating the experimental P response of the upland rice at high N levels. The yield of rice was predicted (r2=0.74 and 0.85) in 2018 and 2019 respectively. Biochar amendments to input parameters for the P model, particularly in relation to P amount and uptake for subterranean soil layers were enhanced and fit between experimental and predicted results. The findings showed that cowpea intercrop could be combined with three different sources of biochar to improve soil fertility and crop productivity in areas where N and P are restricted. APSIM performed well in predicting the growth of cowpea well-supplied with P, and the residual biochar and N benefits to a succeeding upland rice crop, including the response to additional inputs of N fertilizer.
Keywords: Keywords: Agricultural Production Systems sImulator (APSIM), soil layer, biochar, amendment